On the Effect of Modifications to Montmorillonite for the Desulphurization of Synthetic Gasoline - Ying Zhang; Aiping Chen; Chunzhong Li; Meifang Luo; Zhenliang Xu (Adsorption Science & Technology)
The preparation, characterization and desulphurization of hexadecyltrimethylammonium bromide (CTAB)-intercalated montmorillonite (CTAB-MMT) and SiO 2 Ce-pillared montmorillonite (SiO 2 Ce-MMT) is described. CTAB-MMT, SiO 2 Ce-MMT and MMT (the original clay) were examined for their ability to remove thiophene sulphur from normal heptane solution as well as from synthetic gasoline. The adsorption thermodynamics and kinetics on all three adsorbents were investigated when it was found that SiO 2 Ce-MMT possessed a higher adsorption capacity than MMT and CTAB-MMT. The adsorption capacity increased as the temperature increased in the range 303–333 K. The data for the adsorption equilibrium were well fitted by the Freundlich isotherm model. Negative values of ΔG 0 suggested that the adsorption process was spontaneous. Furthermore, positive ΔH 0 and ΔS 0 values indicated that the adsorption was endothermic and irreversible.